Review: efficacy of alginate supplementation in relation to appetite regulation and metabolic risk factors: evidence from animal and human studies. Issue 2 (12th November 2012) - Georg Jensen, M.; Pedersen, C.; Kristensen, M.; Frost, G.; Astrup, A.
Summary This review provides a critical update on human and animal studies investigating the effect of alginate supplementation on appetite regulation, glycaemic and insulinemic responses, and lipid metabolism with discussion of the evidence on potential mechanisms, efficacy and tolerability. Dependent on vehicle applied for alginate supplementation, the majority of animal and human studies suggest that alginate consumption does suppress satiety and to some extent energy intake. Only one long‐term intervention trial found effects on weight loss. In addition, alginates seem to exhibit beneficial influence on postprandial glucose absorption and insulin response in animals and humans. However, alginate supplementation was only found to have cholesterol‐lowering properties in animals. Several mechanisms have been suggested for the positive effect observed, which involve delayed gastric emptying, increased viscosity of digesta and slowed nutrient absorption in the small intestine upon alginate gel formation. Despite reasonable efficacy and tolerability from the acute or short‐term studies, we still realize there is a critical need for development of optimal alginate types and vehicles as well as studies on further long‐term investigation on alginate supplementation in humans before inferring that it could be useful in the management of obesity and the metabolic syndrome.